A Double Edged Sword Role of Interleukin-22 in Wound Healing and Tissue Regeneration - Arshad, Tanzeela; Mansur, Fizzah; Palek, Richard; Manzoor, Sobia; Liska, Vaclav (Frontiers in Immunology, 2020)
Wound healing and tissue regeneration is an intricate biological process that involves repair of cellular damage and maintenance of tissue integrity. Cascades involved in wound healing and tissue regeneration highly overlap with cancer causing pathways. Usually, subsequent tissue damage events include release of a number of cytokines to accomplish post trauma restoration. IL-22 is one of the cytokines that are immediately produced to initiate immune response against several tissue impairments. IL-22 is a fundamental mediator in inflammation, mucous production, protective role against pathogens, wound healing and tissue regeneration. However, accumulating evidence suggests pivotal role of IL-22 in instigation of various cancers due to its pro-inflammatory and tissue repairing activity. In this review, we summarize that how healing effects of IL-22, when executed in an uncontrollable fashion can lead to carcinogenesis.